Computational approaches in cheminformatics and bioinformatics - Guha, Rajarshi; Bender, Andreas (Wiley, 2012)
"Computational Approaches in Cheminformatics and Bioinformatics explores for the first time the unique connection between cheminformatics and bioinformatics. This revolutionary resource demonstrates how integrating these two seemingly different disciplines allows one to computationally address discovery and identification of biological systems in relation to future development. Additionally, the book includes insights from experts from public (NIH), academic, and industrial sources (Novartis, Pfizer). Scientists will find this ground-breaking book essential to the advancement of drug discovery and the issue of chemical control and manipulation of such systems"--